2016
DOI: 10.3945/ajcn.116.142430
|View full text |Cite
|
Sign up to set email alerts
|

Girls’ picky eating in childhood is associated with normal weight status from ages 5 to 15 y

Abstract: Background: Picky eating has been associated with lower weight status and limited food intake and variety in childhood. Little is known about how the persistence of picky eating in childhood is associated with changes in weight and food intake from childhood into adolescence. Objective: We determined whether picky eating identified in childhood was related to growth, nutrition, and parental use of pressure over a 10-y period. Design: Non-Hispanic white girls (n = 181) participated in a longitudinal study and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 25 publications
6
37
0
1
Order By: Relevance
“…It is also of note that the non-picky children in ALSPAC had a growth trajectory well above the 50 th centile of the growth charts so it is possible that in a population in which the children's growth was generally closer to the 50 th centile the trajectories of the picky eaters would be below the 50 th centile and therefore of greater concern. Similar results to those in the ALSPAC study in the UK were found in a group of US girls up to age 15 years, in whom picky eaters tracked about 15 centile points below the non-picky girls who tracked along the 65 th centile (38) . This difference in the location of the trajectories relative to the centiles could reflect a difference in the prevalence of overweight and obesity in the two cohorts and/or the use of different centile charts.…”
Section: Health and Developmentsupporting
confidence: 84%
See 2 more Smart Citations
“…It is also of note that the non-picky children in ALSPAC had a growth trajectory well above the 50 th centile of the growth charts so it is possible that in a population in which the children's growth was generally closer to the 50 th centile the trajectories of the picky eaters would be below the 50 th centile and therefore of greater concern. Similar results to those in the ALSPAC study in the UK were found in a group of US girls up to age 15 years, in whom picky eaters tracked about 15 centile points below the non-picky girls who tracked along the 65 th centile (38) . This difference in the location of the trajectories relative to the centiles could reflect a difference in the prevalence of overweight and obesity in the two cohorts and/or the use of different centile charts.…”
Section: Health and Developmentsupporting
confidence: 84%
“…Although this does not capture all the proposed facets of picky eating behaviour, it does avoid the difficulty of forcing the caregiver to use their own definition of picky eating, and is similar to what might be asked of a parent by a healthcare provider. (2) This question, which is similar to that used in other recent studies (5; 14; 15) , was asked at four timepoints in ALSPAC (24,38,54 and 65 months old), which enables both identification of picky eaters at a single time point and identification of persistent picky eaters, who may be more at risk of adverse health and developmental outcomes than transient picky eaters. It also enables modelling of outcomes that occur after the exposure, enabling a greater degree of confidence in the causality of associations than in a strictly cross-sectional approach.…”
Section: Several Of These Questionnaires Have Been Validated Examplementioning
confidence: 99%
See 1 more Smart Citation
“…In Dutch children measured at age 9, picky eaters (n=403) where shorter, more likely to be underweight and less likely to be overweight than non-picky eaters (n=621) [106]. In a US sample of girls followed from age 5 to 15 years, persistent picky eaters (n=33) had lower BMI than non-fussy children (n=148) [112]. Nevertheless, an important observation was that the fussy eaters' BMI tracked the 50 th percentile, whereas the non-fussy eaters' BMI tracked the 65 th percentile.…”
Section: Implications For Children's Health and Weightmentioning
confidence: 97%
“…Certain studies have shown that children of pre-school age with obesity are more picky than normal-weight children (25) , and that picky eaters have a higher intake of savoury snacks and sweets (risk factors for obesity) at age 14 months (26) . However, other studies have shown a relationship between picky eating and underweight status (12,27) . A systematic review of forty-one studies examining the relationship between picky eating and weight found that the evidence is conflicting, and this may be partially due to the inconsistencies in the measurement of picky eating (28) .…”
Section: Discussionmentioning
confidence: 87%